Empowering Nagari through the Strategic Role of Focal Points in Disseminating Digital Information in Nagari VII Koto Talago, West Sumatra - Ganefri Ganefri; Erianjoni Erianjoni; Ahmaddul Hadi; Mira Hasti Hasmira; Titen Darlis Santi; Alfajri Yusra (Science and Environmental Journal for Postgraduate, 2024)
The growth of information technology has changed the social, economic, and cultural landscape globally, but the challenges of access and distribution of digital information remain significant, especially in rural areas such as Nagari VII Koto Talago. Through community service activities that focus on socialization, training, and workshops on using the Nagari Informative Application, participants can improve their understanding and skills in utilizing information technology. It is hoped that the use of this application will increase efficiency in the delivery of information and public services. The impact evaluation will be important to measure the effectiveness of the use of information technology in improving the performance of the Nagari government and public services, as well as to develop further policies and strategies to support economic, social, and cultural growth in Nagari VII Koto Talago and similar areas throughout Indonesia.